Pemberdayaan Usaha Keripik Singkong Sebagai Usaha Peningkatan Kesejahteraan Masyarakat Di Desa Bangun Purba Kecamatan Deli Serdang Sumatera Utara - Muhammad Andi Prayogi; Adek Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The development and empowerment of the potential possessed by each village or area must continue to be carried out in an effort to improve the welfare of the existing community. Existing potential must be maximized, not left alone. The need for assistance is not only in terms of the manufacturing process, but also the process of making attractive packaging and where the target market is going. Bangun Purba Village is located in Deli Serdang Regency, North Sumatra. This village has potential that needs to be developed in an effort to introduce the MSME products they produce. Community improvement and empowerment is our shared responsibility, not only the government has a role. The method used in this community empowerment uses observation (Observation), training and mentoring, packaging making, promotion and marketing strategies, evaluation of sales results. An increase in the production and sales of cassava chips in Bangun Purba Village, Deli Serdang Regency, North Sumatra, improves the welfare of the local community, this increase is marked by the increasing number of production results which previously were 500 packs per day to 800 packs per day. The marketing method uses whatsapp, facebook, stalls to stalls and uses resellers (resellers). The existence of a good packaging design increases the sales of cassava chips in Bangun Purba Village, Deli Serdang Regency, North Sumatra. The formation of a reliable entrepreneur must be fostered from an early age. Academics can assist the community in the development or management of existing resources in the community in order to improve the welfare of the community itself.